2016
DOI: 10.1016/j.compscitech.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Structure, rheological, thermal conductive and electrical insulating properties of high-performance hybrid epoxy/nanosilica/AgNWs nanocomposites

Abstract: A facile and effective approach by incorporating silica nanoparticles (SNPs) to fabricate high performance epoxy-based electronic packaging materials which are both thermally conductive and electrically insulating was presented. Because of the strong interaction between SNPs and silver nanowires (AgNWs), uniformly dispersed SNPsmodified epoxy was employed to promote the dispersion of AgNWs in epoxy matrix. Further, the enhanced modulus of epoxy matrix by the incorporation of SNPs effectively alleviates the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…Similar phenomenon was also observed in Ref. [221] that by coating PVP on the surface of silver nanowire fillers could hinder their aggregation in a silver-nanowire@epoxy nanocomposite. Unfortunately, it remains very challenging to simultaneously achieve strong filler-matrix coupling and low aggregation.…”
Section: Improvement Of Filler Distributionsupporting
confidence: 87%
“…Similar phenomenon was also observed in Ref. [221] that by coating PVP on the surface of silver nanowire fillers could hinder their aggregation in a silver-nanowire@epoxy nanocomposite. Unfortunately, it remains very challenging to simultaneously achieve strong filler-matrix coupling and low aggregation.…”
Section: Improvement Of Filler Distributionsupporting
confidence: 87%
“…[2][3][4][5][6][7][8][9][10] A large number of studies have shown that the addition of nanoparticles can enhance the electrical properties of the polymer. [3][4][5][6][7][8][9][10] Takada found that the addition of nano MgO to LDPE can inhibit the accumulation of space charge by adding more deep traps; 8 Xilin Wang found that epoxy resin exhibits nonlinear resistance characteristics above 4000 V cm À1 which can effectively improve the electric eld distortion phenomenon. 10 Du Boxue found that the addition of nano SiO 2 to RTV has a signicant inhibitory effect on the growth of electric branches.…”
Section: Introductionmentioning
confidence: 99%
“…Such improvement is caused by the uniformity dispersed of organo-MMT and geo-fillers and enhanced interfacial adhesion for load transfer from epoxy matrix to organo-MMT and geo-fillers [24]. However, as the temperature increase, all the epoxy-organo MMT contain with 2-8phr kaolin geo-fillers show gradual drop in storage modulus up to 1.881Gpa.…”
Section: Resultsmentioning
confidence: 99%